Automation of trend monitoring of radio-electronic equipment - Путятін, В.П.; Фірсанов, В.В.; Елькін, Б.С. (Eastern-European Journal of Enterprise Technologies, 2010)
Principles of development of the system of automation of process of control and diagnostician of side apparatus of navigation and landing radio electronic are resulted. Estimation is given to economic efficiency of application of such methods and facilities, which is based on abbreviation of time of estimation of the operating conditions of apparatus.